Does Board Gender Diversity Affect Financial Distress - Suprapto, Yandi; Ng, Irvin (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2023)
Females were regarded as incompetent as a leader before the current modern era. But, female in managerial positions has been increasing since 2015. As part of corporate governance, there is only a few research regarding gender diversity’s relationship with financial distress with different results on different context. This research investigates the role of board gender diversity on firms’ financial distress. Multiple linear regression is used as the method of study. In general, board gender diversity does not have any relationship with financial distress in the infrastructure firms. When dissected into 4 sub-sectors, 1 out of 3 sub-sectors with 1 other sub-sector excluded, shown a negative relationship between board gender diversity and financial distress while the other 3 sub-sectors do not show any significant relationship. Keywords: Corporate Governance; Financial Distress; Gender Diversity.